POPULATION DYNAMICS OF TUNA (EUTHYNNUS AFFINIS, CANTOR 1849) IN WESTERN WATERS OF SOUTH SULAWESI - Yunus, Budiman; Suwarni; Parawansa, Basse Siang (International Journal of Research -GRANTHAALAYAH, 2020)
This study aims to determine the population dynamics of tuna including age group, growth, mortality, exploitation rate and yield per recruitment. It was conducted from June to August in West Waters of South Sulawesi. By method of age group using Bhattacharya method with FAO-ICLARM Fish Stock Assessment Tools II (FISAT II) program, growth using Von Bertalanffy’s equation, natural mortality (M) using Pauly’s empirical equation, total mortality (Z) using Beverton and Holt’s equations, fishing mortality (F) by the formula Z = F + M, exploitation (E) using Baverton and Holt’s equations and yield per recruitment (Y/R’) using Baverton and Holt’s equations. The results of research of tuna observed were 737 includes 355 male tunas and 382 female tunas. The estimation of total length ranging from 215 mm to 429 mm. Male tunas are classified into 4 (four) of age groups with a length of 236.67, 272.8, 326.04 and 375.53 mm, respectively. Asymptote length (L∞) = 455.00 mm, growth coefficient (K) = 0.33 and theoretical age (t0) of -0.2377 per year. Total mortality rate (Z) = 1.12 per year. Natural mortality (M) = 0.41 per year, fishing mortality (F) = 0.71, exploitation (E) = 0.63 and yield per recruitment (Y/R’) = 0.0691, while male tunas are classified into 5 (five) of age groups with a length of 235.73, 272.86, 326.89, 360.89 and 408.89 mm, respectively. Asymptote length (L∞) = 453.50 mm, growth coefficient (K) = 0.42 and theoretical age (t0) of -0.1853 per year. Total mortality rate (Z) = 1.35 per year. Natural mortality (M) = 0.48 per year, fishing mortality (F) = 0.87, exploitation (E) = 0.64 and yield per recruitment (Y/R’) = 0.0784. Thus, it can be concluded that tuna in West Waters of South Sulawesi have declined and thought occur overfishing.